2020
DOI: 10.3390/cancers12113357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Minimal Extrathyroidal Extension on Early Response Rates after (Adjuvant) Initial Radioactive Iodine Therapy in PTC Patients

Abstract: Background: Extrathyroidal extension of differentiated thyroid cancer is a poor outcome factor but seems to be less significant in minimal extrathyroidal extension (mETE). However, the impact of mETE on response rate after (adjuvant) initial radioactive iodine (RAI) therapy remains unclear. We therefore compared response rates of patients with classical and follicular variants of papillary thyroid cancer (PTC) according to the updated eighth tumor-node-metastasis (TNM) classification to a control group. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Concerning the 10/30 (33.3%) patients who had mETE at surgery, it resulted that also this risk factor is associated with a poor prognosis (p = 0.027) and at the univariate analysis the affected patients showed an increased risk for metastasis appearance after thyroidectomy, OR 3.25 (95% CI 1.13-9.41), p-value = 0.03. These results referring to the few cases of the present study confirm previous data reported in the literature [9,[17][18][19][20][21] while differing from others [13,[22][23][24][25][26][27][28]. Moreover, the primary tumor size of mETE patients was >15 mm in 9/10 (90%) of cases and <10 mm in the remaining case, the latter being a microcarcinoma (8 mm).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Concerning the 10/30 (33.3%) patients who had mETE at surgery, it resulted that also this risk factor is associated with a poor prognosis (p = 0.027) and at the univariate analysis the affected patients showed an increased risk for metastasis appearance after thyroidectomy, OR 3.25 (95% CI 1.13-9.41), p-value = 0.03. These results referring to the few cases of the present study confirm previous data reported in the literature [9,[17][18][19][20][21] while differing from others [13,[22][23][24][25][26][27][28]. Moreover, the primary tumor size of mETE patients was >15 mm in 9/10 (90%) of cases and <10 mm in the remaining case, the latter being a microcarcinoma (8 mm).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, extrathyroid tumor extension (ETE) has been recognized as a prognostic factor of DTC [13,14]. However, while extended ETE (eETE) proved a significant worsening of the prognosis [13][14][15][16], the impact of minimal ETE (mETE) is controversial presenting an increased risk of recurrence in some studies [8,[17][18][19][20][21] and vice versa reporting no significant impact on disease-free survival in other studies [13,[22][23][24][25][26][27][28]. DTC has slow growth and recurrences and metastases can appear and become clinically evident even many years later; thus, the carcinomas can require a long-term follow-up to guarantee careful surveillance of the affected patients [10,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these similarities, minimal ETE and aggressive histopathological features, such as thyroid capsule infiltration, are significantly more common in CPTC than in FVPTC ( 11 ). Besides, patients with mETE showed significantly higher rates of lymph node metastases in the neck ( 12 ) and all levels of ETE, including microscopic ETE, were associated with increased risk for lymph node metastasis and DM ( 13 ). Thus, we propose the following hypothesis: The high DM rate in pediatric PTC aged less than 18 years old is associated with histopathological subtype.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the study showed that age > 55 years did not have a significant impact on the risk of disease. In other studies, it has been observed that radioiodine therapy had a similar response rate in PTC patients regardless of the presence of mETE, although there was a high frequency of LN metastases [37]. According to the results obtained by other authors who reported that mETE increases the risk of recurrence in DTC patients, it has been observed that the absolute increase is small and, in addition, mETE has no impact on disease-related mortality [38].…”
Section: Discussionmentioning
confidence: 91%